Desertion of nursing students in four peruvian universities - Sanabria, Hernán (2002)
Objective: To determine the risk factors associated to desertion of nursing studies in some universities of Peru, as well as to determine the magnitude according to each risk factor. Design: Case-control epidemiological study done during 1999-2000. Material and methods: The following risk factors were studied: health, economy, personal, familial, vocational, working, police-judicial, academic and adaptation to the university life. The sample consisted of 88 cases distributed as follows: 24 students from Huacho and Iquitos and 20 from Lima and Trujillo. The sample did not include students from San Marcos University as there was no approval from the Nursing Department and the Faculty of Medicine. Control students were 65 no desertor students from the same institutions. Results: Most desertion associated risk factor according to OR and its lower CI 95% higher than 1 was the vocational, followed by the economical and the academic factors. Forty two per cent of the students hadn't vocation and 36% economical problems. Conclusions: There is a high association between vocation and economy as well as a light to moderate association of low academic performance and desertion of nursing students in the universities studied.